Improved Processability and Antioxidant Behavior of Poly(3-hydroxybutyrate) in Presence of Ferulic Acid-Based Additives - Lionel F. Longé; Laurent Michely; Antoine Gallos; Agustin Rios De Anda; Henri Vahabi; Estelle Renard; Michel Latroche; Florent Allais; Valérie Langlois (Bioengineering, 2022)
Poly(3-hydroxybutyrate), PHB, has gathered a lot of attention for its promising properties—in particular its biobased nature and high biodegradability. Although PHB is prime candidate for the packaging industry, the applications are still limited by a narrow processing window and thermal degradation during melt processing. In this work, three novel additives based on ferulic acid esterified with butanediol, pentanediol, and glycerol (BDF, PDF, and GTF, respectively) were used as plasticizers and antioxidative additives to improve mechanical properties of PHB. Elongation at break up to 270% was obtained in presence of BDF and the processing window was improved nearly 10-fold. The Pawley method was used to identify the monoclinic space group P2 of the BDF. The estimated crystallite size (71 nm) agrees with a crystalline additive. With PHB70BDF30 blends, even higher elongations at break were obtained though dwindled with time. However, these properties could be recovered after thermal treatment. The high thermal stability of this additive leads to an increase in the fire retardancy property of the material, and the phenolic structure induced antioxidant properties to the samples as demonstrated by radical scavenging tests, further highlighting the possibilities of the PHB/additive blends for packaging applications.